An intracameral injection of antigen induces in situ chemokines and cytokines required for the generation of circulating immunoregulatory monocytes. - Roshan Pais (Public Library of Science (PLoS), 2012)
Anterior Chamber-Associated Immune Deviation (ACAID) induced by an intracameral injection of antigen generates antigen-specific regulatory splenic T cells that suppress specifically cell-mediated immunity specific for the injected antigen. Circulating F4/80(+) cells recovered from mice receiving an intracameral injection of antigen are thought to be ocular in origin and induce the development of thymic and splenic regulatory T cells. We have shown previously that after the intracameral injection of antigen there is a CCR2/CCL2-dependent infiltration of circulating F4/80(+) cells into the anterior chamber associated with the generation of circulating, ACAID-inducing F4/80(+) monocytes. Here we tested the hypothesis that the intracameral injection of antigen induces events in the anterior chamber that are associated with the induction of circulating immunoregulatory monocytes that induce the suppression of cell-mediated immunity. The intracameral injection of antigen resulted in aqueous humor (i) a time- dependent increase of CCL2 and CCL7, (ii) a transient increase in TNF-α, and (iii) an infiltration of CD11b(hi), Gr1(hi) and F4/80(+) as well as F4/80(-) and Gr1(hi) peripheral blood cells into the anterior chamber. Further characterization of these F4/80(+) cells revealed that they are Ly 6C(hi), LY6G(lo) or negative, 7/4 (LY6B)(hi), CD115(+), CD45(+), CD49B(+), and CD62 L(+). Antibody-mediated neutralization of TGF-β in situ in the anterior chamber prevented the induction of circulating, ACAID-inducing monocytes and ACAID. These cells did not increase in the irides of ACAID-refractory CCR2-/- and CCL2-/- mice that received an intracameral injection of antigen. Our results extend our suggestion that ACAID is initiated as the result of a mild proinflammatory response to intracameral injection that results in the infiltration of a CCR2(+) subset of monocytes into the anterior chamber where there is a TGF-β-dependent induction of an immunosuppressive phenotype in the infiltrated monocytes that recirculate to induce antigen-specific regulatory T cells.